Insights from Analysis of Binding Sites of Human Meprins: Screening of Inhibitors by Molecular Dynamics Simulation Study - Chaudhuri, Ankur; K. Bera, Asim; Sarkar, Indrani; Chakraborty, Sibani (Combinatorial Chemistry & High Throughput Screening, 2016)
Human meprin-α and-β are important regulators of angiogenesis, cancer, inflammation, fibrosis, and neurodegenerative diseases and hence important therapeutic targets. Meprins are the only astacin proteases that are expressed in membrane-bound and secreted form. The cleavage specificity of human meprins is similar in certain cases but differs markedly in others. The inhibitor selectivity of human meprins is controlled by the specific residues involved in binding at the active-site cleft of the proteases. Meprins are inhibited by various small molecular inhibitors as well as macromolecular endogenous inhibitors, making them good drug targets. In the current study, molecular dynamics simulation was performed for 10 ns on ten systems consisting of two apoenzymes of meprin -α/β and eight complexes of human meprin-α and -β complexed to four inhibitors with different metal binding moieties and comparable Ki values. These simulation studies helped to elucidate the molecular details of how several parameters influence protein–inhibitor binding affinity. Analysis of the interaction energies of the protein–inhibitor complexes revealed the diverse binding nature of this series of inhibitors. Several structural segments of human meprins exhibited certain conformational changes during the simulation time course. Among the inhibitors studied captopril had a different disposition in the meprin-bound complexes compared to the other three inhibitors, namely Pro- Leu-Gly-hydroxamate, galardin and EDTA. Comparison of the interaction energies for each system helped us to conclude that the hydroxamic acid-based inhibitors are the most potent inhibitors of meprins.
Keywords: dynamics simulation